Economic Analysis of the Management of the Nuclear Spent Fuel in Spain - B. Yolanda Moratilla Soria; David Echevarria-Lopez (Science and Technology of Nuclear Installations)
This study aims to analyze the economic and technical viability for either nuclear fuel reprocessing or permanent storage in Spain. Utilizing various international studies regarding nuclear fuel reprocessing, this study reaches an objective conclusion while taking into consideration the various variable and stable costs for the open and closed cycles. A sensitivity analysis was then introduced which identifies the most influential parameters in the final price. This analysis is essential in understanding the results obtained and emphasizes the need to specify a range of costs for both cycles and to see what factors affect these results. The sensitivity analysis describes the factors that play a large role in determining costs and will display the range of values that arise from the variability of costs for those factors. The uncertainty analysis compares the nominal values used in this study and describes how these values are likely to change with time resulting in a range of values for both cycles.